The secret of rendering signs effective: the import of C. S. Peirce’s semiotic rhetoric - Bergman, Mats (Public Journal of Semiotics, 2007)
In this article I trace the historical development of Peirce’s semiotic rhetoric from its early appearance as a sub-discipline of symbolistic to its mature incarnation as one of the three main branches of the science of semiotic, and argue that this change in status is a symptom of Peirce’s broadening semiotic interest. The article shows how the evolution of Peirce’s theory of signs is linked to changes in his conception of logic. This modification is not merely a minor justification in his classification of the sciences; rather, it indicates a growing understanding of the interconnection between the different semiotic sub-disciplines. The scope and character of the mature discipline of rhetoric is further discussed in terms of a possible clash between rhetorical and methodological emphases, and a conciliatory strategy is suggested. The article concludes with some reflections on the relevance of Peircean rhetoric for future work in Peirce studies and semiotics.